ANALYSIS OF STUDENT AND TEACHERS BEHAVIOR ON BIOLOGY LEARNING PROCESS AT SECOND GRADERS OF NATURAL SCIENCE OF ENSINO SECUNDÁRIO 4 DE SETEMBRO UNAMET DILI - TIMOR LESTE - PINTO, TERESA (IJRDO- Journal of Educational Research, 2017)
Research Objectives 1) Knowing the behavior of students in the process of learning Biology. 2) Knowing Master’s behavior in biology learning process. 3) Knowing the teacher’s performance in the biology learning process. 4) Knowing Master’s motivation to improve student’s achievement in Biology learning. 5) Knowing the supporting and inhibiting factors that influence student’s and teacher’s behavior in the biology learning process. This research was conducted by using qualitative descriptive method. Data collection techniques implemented by interactive and inter subjective. This technique is used to explore in the field with the approach of communicative action using field observation techniques or participant observation/participant observation, interview and documentation study. The results showed that "Students are the main actors in learning, so that the learning process should be their social so that students’ ability in terms of cognitive, affective, and cognitive will experience the development. Teachers as educators and mentors for students then teachers have an important role in improving student achievement. To find out student achievement then the indicator is used as a benchmark in stating that a teaching and learning process can be said to succeed. In communication and attitude changes will always be done in the learning by teachers and students. In a learning teacher and students together become actors for the implementation of learning objectives.